Cohomology and formal deformations of $n$-Hom–Lie color algebras - Abdaoui, K.; Gharbi, R.; Mabrouk, S.; Makhlouf, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5The aim of this paper is to provide a cohomology of $n$-Hom–Lie color algebras, in particular,  a cohomology governing one-parameter formal deformations.  Then we also study formal deformations of the $n$-Hom–Lie color algebras and introduce the notion of Nijenhuis operator on a $n$-Hom–Lie color algebra, which may give rise to infinitesimally trivial $(n-1)$-order deformations.  Furthermore, in connection with Nijenhuis operators, we introduce and discuss the notion of product structure  on $n$-Hom–Lie color algebras.